If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(6x + -11) = -5 Reorder the terms: x(-11 + 6x) = -5 (-11 * x + 6x * x) = -5 (-11x + 6x2) = -5 Solving -11x + 6x2 = -5 Solving for variable 'x'. Reorder the terms: 5 + -11x + 6x2 = -5 + 5 Combine like terms: -5 + 5 = 0 5 + -11x + 6x2 = 0 Factor a trinomial. (5 + -6x)(1 + -1x) = 0Subproblem 1
Set the factor '(5 + -6x)' equal to zero and attempt to solve: Simplifying 5 + -6x = 0 Solving 5 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 0 + -5 -6x = 0 + -5 Combine like terms: 0 + -5 = -5 -6x = -5 Divide each side by '-6'. x = 0.8333333333 Simplifying x = 0.8333333333Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {0.8333333333, 1}
| x/-16=-10 | | 23+4=83 | | 3.1415926535897932384626433832795028841971693993751058209749445923078164062862089986280348253421170679821480865132823066470938446095505822317253594081284811174502841027019385211055596446229489549303819644288109756659334461284756482337867831652712019091456 | | 0.8(1.2+5)= | | 4a*2-9b*2+a*2-1+2b*2+5= | | 5x+4=4x-7 | | 3.1415926535897932384626433832795028841971693993751058209749445923078164062862089986280348253421170679821480865132823066470938446095505822317253594081284811174502841027019385211055596446229489549303819644288109756659334461284756482337867831652712019091456 | | 3(x-7)=3x-7(7-x) | | 3r*2r= | | B/13-3b/13=8/23 | | -x^2+6x+34=0 | | -0.3(x-4)+x=1.5+-0.5x | | 6x*4x= | | -6(-17)= | | -397h=16t^2 | | ((5/8)x^2)-8x+72.5=0 | | (5a)2= | | 18x+30= | | 4y+9=-7 | | (5/8)x^2-8x+72.5=0 | | 16=2x+2(x-2) | | v-8=3 | | x^2-x+1/4=x/4 | | x^2-6x+9+y^2+2y+1=32 | | 8d-1/3(6-9d)=42 | | 6x+4(x-3)=48 | | 3*3.14d=12*3.14 | | ln(y)=.63 | | h(3)=400-16t^2 | | 7n-2=6n-2n | | (f+4)/2=5 | | 49k^2x-16y-16x+49k^2y=0 |